NILAI KETAKTERATURAN TOTAL SISI DARI GRAF TUNAS KELAPA - A, Moch. Zaenal; Slamin, S; Setiawani, Susi (KadikmA, 2014)
Abstract. A total edge irregular labeling on a graph G which has |E| edges and |V| vertices is an assignment of positive integer number as labels to both vertices and edges so that the weights calculated at every edges are distinct. The weight of an edge xy in G is defined as the sum of the label of xy and the labels of two vertices x and y, that is w(xy) = ï¬(x)+ ï¬(xy)+ ï¬(y). The total edge irregularity strength of G, denoted by tes(G), is the smallest positive integer k for which G has an edge-irregular total k-labelling. In this paper, we determine the exact value of the total edge (vertex) irregularity strength of Coconut Sprout Graph (CRn,m) and the union of isomorphic and non-isomorphic Coconut Sprout Graph. Key Words : total edge irregular labeling, total edge irregularity strength, coconut sprout graph.